An Analysis of Metaphor in Maya Angelouâ€™s â€œCaged Birdâ€ and â€œStill I Riseâ€ Poems - Akhbar Pradana Raharta; Waode Hamsia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2016)
This research explored the possible meaning of the metaphor in the poem of Maya Angelou. The researcher focused on metaphor forms found as the object to be analyzed in Maya Angelou’s poems. Metaphor is one part of figurative languages which is the most common and widely used in literary works such as poem. Poem is a media for a poet to express feeling and imagination based on condition of a poet’s life. The data of this research were Caged Bird and Still I Rise poems by Maya Angelou. This research used descriptive qualitative to analyze the data. The purpose of this research was to find out the type of metaphor based on Crystal, Lakoff and Johnson theory, know the reasons of the use of metaphor, and interpret the poem meaning based on explication and author’s biography. It was found that Maya Angelou used three types of live metaphor they are Conceptual metaphor, Mixed metaphor and Poetic metaphor. It was also found that each poem tells about the author’s personal opinion about the racial inequality between black races and white races in America at that time.